Peranan industri sub sektor perhotelan terhadap penyerapan tenaga kerja di Provinsi Jambi - Christina Maya Lestari; Zulfanetti Zulfanetti; Dearmi Artis (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2019)
This study aims to determine the effect of Number of Hotels, Number of Rooms, Room Occupancy Rates, Minimum Wages on employment opportunities in Hotels in Jambi Province. This study uses an Ordinary Least Squares (OLS) multiple regression analysis model.Based on the results of the regression analysis, it is known that the variable number of hotels and minimum wages has a significant effect on the level of employment in Jambi Province, while the variable number of rooms and occupancy rates have no significant effect on the employment of industrial labor in the hotel sub-sector in Jambi Province. Keywords: Number of Hotels, Number of Rooms, Occupancy Rate, Minimum Wage, Absorption of Labor.